3D point cloud of the Hundsalm ice cave - Jan Pfeiffer; Martin Rutzinger; Christoph Spötl (PANGAEA, 2022)
3D point cloud of the Hundsalm ice cave acquired with a Riegl VZ-2000i Terrestrial Laser Scanner on 2020-05-15, 2020-06-23 and 2020-07-03. Individual point clouds acquired from 255 scan positions were co-registered taking into account potential changes in snow, firn and ice content between the acquisition campaigns. The final data set reflects the snow, firn and ice conditions of 2020-07-03 and contains 3D points with an average spatial resolution of 2 cm. Points are classified into 4 classes: 1 = above ground points (e.g. vegetation) outside the cave, 2 = ground points outside the cave, 3 = points representing the cave extquotesingles rock surface, 4 = points representing the snow, firn and ice surface in the cave. The points are stored in ETRS89/UTM zone 32N coordinates (EPSG:25832) and include, beside of the classification, an intensity attribute.